2000
DOI: 10.1055/s-2000-8388
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Free Flaps for Reconstruction After Resection of Congenital Arteriovenous Malformations of the Hand

Abstract: Between 1981 and 1996, the authors performed reconstructions with vascularized free flaps in four patients with congenital arteriovenous malformations of the hand. This series included one man and three women, whose ages at the time of surgery ranged from 20 to 57 years, with an average of 41 years. All were categorized as fast-flow type B malformations. The locations of the arteriovenous malformations were the thumb only, thumb to palm, index to palm, and thumb and index to palm. In all cases, free vasculariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The concept of regulating flap, that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types clearly prevent the recurrence or regrowth compared with skin grafts…”
Section: Resultsmentioning
confidence: 99%
“…The concept of regulating flap, that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types clearly prevent the recurrence or regrowth compared with skin grafts…”
Section: Resultsmentioning
confidence: 99%
“…The concept of a regulating flap, that reconstruction using a free flap controls the recurrence or regrowth after resection of AVM, has been proposed. However, no report has evaluated whether free flaps and other flap types clearly prevent the recurrence or regrowth compared with skin grafts…”
Section: Resultsmentioning
confidence: 99%
“…Of these 4 reported cases of VMs involving the thumb, the resultant defects after radical resection were relatively small in 2 patients, involving only the distal phalanx of the thumb and requiring reconstruction with a free toe pulp flap 8 and a wraparound flap. 11 Even the 2 patients with more extensive defects involving the thumb still had an intact bony skeleton and flexor and extensor tendons and required only soft tissue reconstruction with an extended wraparound flap. 10,12 None of these 4 malformations approached the size of the VM presented here, which was truly massive and not only prevented pinch and grip function of the hand but also compromised elbow and shoulder function because of its weight.…”
Section: Discussionmentioning
confidence: 99%
“…5 Other case reports and small series have suggested that radical excision and free flap reconstruction may prevent recurrences. [7][8][9][10][11][12] Radical resection of vascular malformations may result, however, in an extensive anatomic and functional defect. We report a young child with a massive VM involving the thumb, first web space, and index finger treated by radical resection and immediate reconstruction with a second toe transfer.…”
mentioning
confidence: 98%